SYSTEM AND METHOD FOR MANAGING CACHED OBJECT WITH NOTIFICATION BOND ON DISTRIBUTED FILE SYSTEM - ALMEIDA, DANILO D'AMICO; PARDIKAR, SHISHIR PURUSHOTTAM; STEERE, DAVID CAPPERS; KUMAR, ROHAN; LIN, YUN (2004)
PURPOSE: A system and a method for managing a cached object with notification bond on a distributed file system are provided to enable a client to cache a lot of objects and synchronize the cached objects with corresponding objects of a server quickly. CONSTITUTION: The server(103) includes a file system manager(107) for managing the object(109) and a bond manager(105) for issuing the notification bond to the client. Each notification bond enables the client to obtain notification from the server by responding to an object related event associated with the original object. The bond manager includes a filter component to determine the object related event by monitoring communication traffics related to the file system manager.